Splenic hydatic cyst as a cause of sinistral portal hypertension and isolated gastric variceal bleeding - Bülent KANTARÇEKEN; Ali ÇETİNKAYA and Ertan BÜLBÜLOĞLU and Gülen DEMİRPOLAT (Turkish Journal of Gastroenterology, 2019)
-